Optimized non-toxic double absorber perovskite solar cell with efficiency beyond 33% - Sheikh Hasib Cheragee; Jannatul Afroj Akhi; Mishion Dev; Md. Mahfuzul Haque; Md. Alomgir Kabir; Tamim Hossain; Mohammad Tahsin Alam; Mohammad Jahangir Alam (Results in Optics)
Lead-based perovskite solar cells (PSCs) have demonstrated significant potential; however, their use has been limited due to concerns about stability and toxicity. To address these issues, this study explores a double absorber solar cell (DASC) composed of Cs2TiBr6 and La2NiMnO6 as an alternative to lead-based perovskite absorbers. These materials offer both safety and stability advantages. The research employs the SCAPS-1D modeling program to propose a new double absorber perovskite photovoltaic cell architecture, which includes TCO, TiO2, Cs2TiBr6, La2NiMnO6, Cu2O, and Au layers. The study investigates how various parameters, such as the electron transport layer (ETL), absorber layer, temperature, light spectra, and defect density affect the performance of the proposed cell structure. Initial optimization of the cell characteristics was conducted with a constant defect density. After achieving the optimal configuration, the defect concentration was varied to assess its impact on cell functionality. Device modeling indicates that the proposed design performs effectively at a temperature of 300 K, with the optimal thickness for the La2NiMnO6 absorber estimated to approximately 0.8 µm under AM 1.5G 1 sun illumination. Following current matching by adjusting the thickness of perovskite absorbers with different bandgaps, the perovskite/perovskite double absorber devices achieved an efficiency of 33.71 %, with an open circuit voltage (Voc) of 0.9171 V and short circuit current density (Jsc) of 43.83 mA/cm2.